Legal Advocacy For Catfish Cultivation Groups As An Effort To Improve The Economy In Facing The Covid 19 Pandemic In Mojorang Agung Wondayu Village, Sidoarjo, East Java, Indonesia - Sutrisno; Mas Anienda Tien F; Rohmatul Faizah; Hervina Puspitosari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Empowerment of catfish advertising cultivation for the community can increase the income source of rural communities and also as an effort to expand employment opportunities for rural communities through the provision of existing land and water in the village of Mojorangagung Wondayu Sidoarjo, East Java, Indonesia. Fish farming business groups in running their business require a business license as a form of legality. Assistance and roles and cooperation with various related agencies are needed in the progress of fish farming business groups, for example,Cooperation with the Department of Agriculture and Food, Cooperation with Universities, one of which is with the National Development University